2010
DOI: 10.1007/s10534-010-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced heme oxygenase-1 gene expression is associated with the depletion of glutathione in the roots of Medicago sativa

Abstract: Following previous findings that cadmium (Cd) induces heme oxygenase-1 (HO1) gene expression in alfalfa seedling roots, we now show that the decreased glutathione (GSH) and ascorbic acid (AsA) contents, induction of HO-1 gene expression and its protein level by Cd was mimicked by a GSH depletor diethylmaleate (DEM). Meanwhile, above Cd- or DEM-induced decreased GSH content followed by HO-1 up-regulation could be strengthened or reversed differentially by the application of a selective inhibitor of GSH biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 37 publications
(57 reference statements)
4
36
0
Order By: Relevance
“…The role of HO is also noticeable in phytochrome-chromophore synthesis (Terry et al, 1993;Verma and Shekhawat, 2013). In plants, HO1 (co-localized in chloroplast to mitochondria) is a major stress-response protein among HO isoforms (HO1, HO2, HO3, and HO4) Jin et al, 2011;Dixit et al, 2013) and acts as an antioxidant under different abiotic stresses such as UV-B stress (Yannarelli et al, 2006) and cadmium stress (Matsumoto et al, 2004;Cui et al, 2011;Fu et al, 2011). Recent studies in plants demonstrated that HO contributes to alleviating the effects of salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…The role of HO is also noticeable in phytochrome-chromophore synthesis (Terry et al, 1993;Verma and Shekhawat, 2013). In plants, HO1 (co-localized in chloroplast to mitochondria) is a major stress-response protein among HO isoforms (HO1, HO2, HO3, and HO4) Jin et al, 2011;Dixit et al, 2013) and acts as an antioxidant under different abiotic stresses such as UV-B stress (Yannarelli et al, 2006) and cadmium stress (Matsumoto et al, 2004;Cui et al, 2011;Fu et al, 2011). Recent studies in plants demonstrated that HO contributes to alleviating the effects of salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…HO exists in three major isoforms: HO-1, an inducible form, and HO-2/3, two constitutively expressed forms. Similar to the processes in animals, HO was claimed as the potential source of CO in plants as well (Muramoto et al 2002) and acts as a strong antioxidant enzyme in plants against different abiotic stresses as well as function in light signaling (Noriega et al 2004;Cui et al 2010;Davis et al 2001;Gisk et al 2010;Liu et al 2010). Meanwhile, some HO subfamilies have been characterized in Arabidopsis, soybean, tomato, sorghum, rice, pine, etc (Shekhawat and Verma 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The germinating seeds showed higher expression level of MsHO2 than that in other tissues, suggesting that MsHO2 gene may play an essential role in alfalfa seeds germination. In previous studies, HO1 was found responsive to an extensive array of chemical agents and stimuli including heavy metals [1,[6][7][8], glutathione depletion [9], UV radiation [10], salinity stresses [11,12], and H 2 O 2 [13]. However, HO2 is constitutively expressed in all cell types, and the only inducers of the HO2 identified to date are the adrenal glucocorticoids [18].…”
Section: Expression Pattern Analysis Of Msho2 Genementioning
confidence: 99%
“…The first isozyme, HO-1, is inducible by its substrate, heme, as well as by many other stimuli. Indeed, HO-1 could be activated by so many stressful stimuli, including heavy metals [1,[6][7][8], glutathione depletion [9], UV radiation [10], salinity stresses [11,12], and hydrogen peroxide (H 2 O 2 ) [13] in plants. The diversity of HO-1 inducers leads to the speculation that HO-1 may play an important role in maintaining cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%